2013
DOI: 10.1136/vetreccr.164.5.149rep
|View full text |Cite
|
Sign up to set email alerts
|

Emerging canine angiostrongylosis in northern England: five fatal cases

Abstract: nal haemorrhages and prolonged bleeding from wounds or after surgery (Ramsey and others 1996, Brennan and others 2004, Morgan and others 2005). In neurological cases, paresis, depression, seizures, spinal pain, behavioural changes, ataxia and loss of vision have been described as potential results of aberrant nematode migration or subdural haemorrhage (Patteson and others 1993). This short communication reports on five fatal, presumably autochthonous, cases of A vasorum infection in dogs from northern England … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Knowledge of the distribution of A. vasorum in dogs in the UK was based, prior to the present study, either upon published reports of clinical cases seen in southwestern England, south Wales, southeastern England and, more recently, the West Midlands, northern England and Scotland or published lab studies testing large number of serum samples that were originally collected for miscellaneous diagnostic purposes across the UK and subject to secondary testing for the detection of A. vasorum (Jacobs and Prole 1975, Simpson and Neal 1982, Patteson and others 1987, Trees 1987, Chapman and others 2004, Helm and others 2009, Yamakawa and others 2009, Schnyder and others 2013a). Larger-scale clinical studies, such as Blehaut and others (2014), who described a retrospective study of 142 clinical cases, submitted to the Royal Veterinary College between April 1999 and July 2012, have sought to address the distribution of clinical cases on a regional basis (southeastern England).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the distribution of A. vasorum in dogs in the UK was based, prior to the present study, either upon published reports of clinical cases seen in southwestern England, south Wales, southeastern England and, more recently, the West Midlands, northern England and Scotland or published lab studies testing large number of serum samples that were originally collected for miscellaneous diagnostic purposes across the UK and subject to secondary testing for the detection of A. vasorum (Jacobs and Prole 1975, Simpson and Neal 1982, Patteson and others 1987, Trees 1987, Chapman and others 2004, Helm and others 2009, Yamakawa and others 2009, Schnyder and others 2013a). Larger-scale clinical studies, such as Blehaut and others (2014), who described a retrospective study of 142 clinical cases, submitted to the Royal Veterinary College between April 1999 and July 2012, have sought to address the distribution of clinical cases on a regional basis (southeastern England).…”
Section: Discussionmentioning
confidence: 99%
“…Over the following two decades, many more cases were recorded in Wales (Patteson and others 1987, Trees 1987) and southeastern England (Chapman and others 2004). A survey of nematode parasites of wild foxes in England later and more recently in Scotland suggested that the parasite may be spreading further north (Morgan and others 2008, Philbey and Delgado, 2013), and this was supported by a report of five fatal cases of A. vasorum infection in dogs from northern England and the West Midlands (Yamakawa and others 2009), a case in Glasgow (Helm and others 2009) and a laboratory study using serum samples from dogs with a range of conditions across the UK (Schnyder and others 2013a). Yet despite the increasing number of reports of canine angiostrongylosis at a regional level, there has as yet been no attempt to establish the distribution of infection in dogs on a nationwide scale and formally assess potential clustering of cases.…”
Section: Introductionmentioning
confidence: 95%
“…A veterinary practice-based questionnaire identified reports of canine angiostrongylosis in Scotland and northern England, but in lower numbers than further south (Kirk and others 2014), and these could be in dogs originally infected elsewhere. Confirmed records of angiostrongylosis in dogs in the north of England are published but in small numbers and not in the far north of the UK (Yamakawa and others 2009). Further information on the epidemiology of the parasite in the northern UK is needed, to guide efforts to control the disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of data from veterinary clinics distributed throughout the country allows a more extensive picture of disease distribution to be drawn and is the subject of an accompanying paper, in which Kirk and others (2014) show that A. vasorum infection has spread beyond traditional endemic foci and is now widespread in central England with clusters of infection in the southeast of England and South Wales. Such studies complement the discovery of cases from other referral centres including Liverpool (Yamakawa and others 2009) and Glasgow (Helm and others 2009). …”
Section: Discussionmentioning
confidence: 77%